Russian translation reception of B. Disraeli’s fiction in the 1850–1910s; Язык. Общество. Образование - Ажель Ю. П. Юлия Петровна (2024, 2024)
One of the brightest pages in the history of Russian-English literary relations is the Victorian novelist Benjamin Disraeli’s fiction reception in Russia throughout the period of 1850–1910. Being an outstanding representative of silver-fork novels, he won recognition for his literary talent not only in Great Britain, but also abroad. Moreover, most literary scholars consider Benjamin Disraeli as a founder of the English political fiction genre